THE NEGATIVE EFFECTS OF THE CLIMATE CHANGE TO THE CITIES OF UZBEKISTAN - Hakimova , Nigina O‘ktam qizi; Erkinova , Marjona Vahobiddin qizi (Innovative Development in Educational Activities, 2023)
This study examines the impact of global climate change on the environment in the world as a whole, as well as on the Central Asian region and Uzbekistan. It was revealed that climate variability in arid areas negatively affects the state of water and land resources. Climate change carries risks in terms of growing agricultural products, which can lead to changes in agricultural practices. It was revealed that the main challenges for Uzbekistan today and in the future are the reduction of water resources due to climate change and the increase in the need for water in agriculture. Based on the results of the study, it can be concluded that investing in the use of innovative technologies in agriculture, as well as the reconstruction of the existing irrigation infrastructure in the face of climate change, will lead to long-term sustainability of the water sector of Uzbekistan and the use of land resources.